Synthesis, Characterization and Photocatalytic Application of Ultra-Fine a-Fe2O3 Nanofiber - P. Dhal, Jyoti; Mishra, B.G.; Hota*, G. (Asian Journal of Chemistry, 2013)
In this study, we have synthesized ferrous oxalate nanofibers by electrospinning methods using poly(vinyl pyrrolidone)/ethanol polymer solution and ferrous oxalate powder. The ferrous oxalate powder was prepared by chemical precipitation method. The obtained as-spun nanofiber was calcined at 500 ºC to form a-Fe2O3 nanofiber. The formation, phase analysis, surface morphology of the nanofibers were characterized using SEM, EDAX, XRD and FTIR analytical techniques. XRD studies confirmed the formation of a-Fe2O3. The SEM and EDAX analysis indicates the formation of fiber like nanomaterials and the presence of Fe and O elements. The obtained nanofibers were used as catalyst for the photochemical decolourization of toxic organic dye from aqueous solution.